Trade Liberalization with BRICS: A CGE Model of Egypt - Ashraf, Kareem (AUC Knowledge Fountain, 2024)
This paper presents an ex-ante impact assessment of a hypothetical FTA between Egypt and the BRICS from an Egyptian economy-wide and sectorial perspectives, with a granular look into manufacturing. The chosen methodology is a static SAM-based Computable General Equilibrium model calibrated to Egypt’s 2018-2019 Social Accounting Matrix (SAM). With respect to existing literature, the paper uniquely stands in considering an Egypt-BRICS FTA with a granular assessment of manufacturing subsectors and in running a simulation of Egypt’s trade liberalization with the wider BRICS alliance, including the accession of Saudi Arabia, UAE, Ethiopia, and Iran, which joined the bloc along with Egypt in January 2024. Beside the wider BRICS simulation, the model is used to run a simulation with core BRICS members. Magnified upon considering the wider bloc, results predict an increase in real consumption across all household income quantiles with the poor generally reaping more of the welfare gains, defined as the increase in household real consumption. Real GDP expands while inflation is imported on the back of local currency depreciation, implying a positive exchange rate pass-through. On a sectorial level, sectors reliant on local intermediate inputs suffer as they don’t benefit from decreased import prices while still facing foreign competition. On the other hand, sectors with initially competitive export prices thrive on the back of a cheaper local currency.